Zagadnienia procesowego modelu sądowego stosowania prawa: [Problems of the procedural model of the judical application of law] (Studia Prawnicze / The Legal Studies, 1986)
The model of procedural application of law treats the process as a sequence of acts. The model of judicial application of law is constructed on the basis of the civil actions of examinations. The author singles out a simple and a complex model in question.The simple procedural model deals with the proceedings before the first instance court. Three phases are singled out: the phase of instituting proceedings;-the hearing in the "act-aspect", "control-aspect" and "substantive aspect"; the closing phase of process before the first instance.The complex procedural model contains three parts: the simple model, the "transitory mechanisms" linking the proceeding before the first instance with that before the second instance, and the Proceeding before the second instance dealt with analogously as that before the first instance.The proceedings are thought of as controlled by the principles. The author analyses the litterature dealing with the (general) principles of procedure and adds to their enumeration the principle of legality of proceedings and the principle of rationality of decision.Axiological analysis of the procedural model of judicial application of law presents the ways of justifying the singled out principles, viz. the instrumental and the praxiological justification. The former treats principles as means for implementing the basic values of individual and social interest. The latter deals. with effectiveness of the proceedings, and there are three groups of principles having this type of justification, viz. unconditionally praxiologically justified, justified conditionally, and praxiologically neutral principles.Taking into account the axiological basis and the directival function of principles the author singles out three groups of principles: principles of the content of acts, principles of the form of acts, and principles of the subjects of acts.In the conclusion the author analyses the possibilities of extrapolating the model in question for other types of proceedings before the courts, and to all judicial and non-judicial proceedings as well. From the theoretical point of view the construction of such general model is possible provided the proper level of abstraction is used. The purposefullness of the construction of such model depends of the purpose it should serve, e.g. an epistemic, legislative or didactic scope. The possibility in question does not decide the issue of the legislative regulation of legal proceedings on such level of abstraction